Microglia and Stem Cells for Ischemic Stroke Treatment—Mechanisms, Current Status, and Therapeutic Challenges - Aleksandra Markowska; Dariusz Koziorowski; Stanisław Szlufik (Frontiers in Bioscience-Landmark, 2023)
Ischemic stroke is one of the major causes of death and disability. Since the currently used treatment option of reperfusion therapy has several limitations, ongoing research is focusing on the neuroprotective effects of microglia and stem cells. By exerting the bystander effect, secreting exosomes and forming biobridges, mesenchymal stem cells (MSCs), neural stem cells (NSCs), induced pluripotent stem cells (iPSCs), and multilineage-differentiating stress-enduring cells (Muse cells) have been shown to stimulate neurogenesis, angiogenesis, cell migration, and reduce neuroinflammation. Exosome-based therapy is now being extensively researched due to its many advantageous properties over cell therapy, such as lower immunogenicity, no risk of blood vessel occlusion, and ease of storage and modification. However, although preclinical studies have shown promising therapeutic outcomes, clinical trials have been associated with several translational challenges. This review explores the therapeutic effects of preconditioned microglia as well as various factors secreted in stem cell-derived extracellular vesicles with their mechanisms of action explained. Furthermore, an overview of preclinical and clinical studies is presented, explaining the main challenges of microglia and stem cell therapies, and providing potential solutions. In particular, a highlight is the use of novel stem cell therapy of Muse cells, which bypasses many of the conventional stem cell limitations. The paper concludes with suggestions for directions in future neuroprotective research.